PP.16.04: VISCERAL ADIPOSITY INDEX AND CARDIOVASCULAR RISK IN THE ELDERLY. (June 2015) - Marotta, T.; Schettini, F.; Verde, F.; Ferrara, L.A.
Abstract : Objective: To assess the relationship between Visceral Adiposity Index (VAI), a proxy of insulin resistance, and cardiovascular risk in elderly outpatients. Design and method: To assess the relationship between Visceral Adiposity Index (VAI), a proxy of insulin resistance, and cardiovascular risk in elderly outpatients. Results: Mean VAI was 5.30 ± 4.4 in the 493 patients studied (5.44 ± 3.5 in the 381 women, 4.83 ± 2.7 in men, p = 0.088). Median VAI was very similar in the 2 sexes (F = 4.36, M = 4.34). Age (67 ± 6 years in the whole sample), BMI (33.1 ± 6.6 kg/m 2 ), blood pressure (153/85 ± 24/13 mmHg) and estimated glomerular filtration rate (eGFR) (71 ± 16 ml/min/1.73 m 2 ) were not different in patients whose VAI was above (Group A) and below (Group B) median VAI. At variance, Group A patients had higher total cholesterol (224 ± 46 vs 211 ± 40 mg/dL, p < 0.001), non-HDL cholesterol (177 ± 42 vs 150 ± 52 mg/dL, p = 0.001), and uric acid levels (5.4 ± 1.4 vs 5.2 ± 1.3, p = 0.023) than Group B patients. VAI was directly correlated with total and non-HDL cholesterol in the whole sample and in either sex; a direct correlation with blood glucose was also present in women and in the whole sample, but not in men. Conversely, VAI was inversely correlated with age, both in men (r = −0.220, p = 0.02) and in the whole sample (r = −0.120, p < 0.01). Ten-year coronary risk (CR) was assessed by the Framingham equation in patients aged less than 74 years and without history of overt cardiovascular disease (N = 343). CR was higher in Group A (16.1%) than in Group B (11.8%), p < 0.001. The difference was highly significant in women (N = 282, p < 0.001) and approached statistical significance in men (N = 61, p = 0.058). In the stepwise multiple regression analysis, VAI was independently associated with CR and was included in the equation before uric acid, non-HDL cholesterol, and eGFR in this order (r 2  = 0.163). Conclusions: VAI may be a useful parameter in the assessment of cardiovascular risk in elderly outpatients.